(untitled) (Baghdad Science Journal, 2023)
This study explored the development and qualities of the response of electrochemical properties of enrofloxacin-selective electrodes using precipitation based on producing phosphotungstic, after utilizing a matrix of polyvinyl chloride (PVC) and dibutyl phthalate or dibutyl phosphate as a plasticizer. The resulting membrane sensors were an enrofloxacin-phosphotungstic electrode (sensors 1) and an ENR-DOP-PTA electrode (sensors 2). Linear responses of (ENR-DBPH-PTA) and (ENR-DOP-PTA) within the concentration ranges of 2.1×10-6-10-1 and 3.0×10-6-10-2 mol. L-1, respectively, for both sensors were observed. Slopes of 51.61±0.24 and 39.40± 0.16 mV/decade and pH ranges equal to 2.5-8.5 and 2.0-9.0 were observed for sensors 1 and 2, respectively. The coefficients of selectivity of the created sensors demonstrated phenomenal selectivity for ENR. The proposed sensors showed useful scientific properties for the assurance of ENR in drug dosage and pure form.